Google Sites-Assisted Discovery Learning in Primary Mathematics and Its Effect on Students’ Problem-Solving Ability in Factors and Multiples - Maharani, Putri; Andrijati, Noening (Jurnal Paedagogy, 2026)
This study aims to examine students’ mathematical problem-solving skills and determine the effect and contribution of implementing the Discovery Learning model supported by Google Sites on the topics of Greatest Common Divisor (GCD) and Least Common Multiple (LCM) among fourth-grade students at SDN 2 Jampiroso. This research employed a quantitative quasi-experimental method using a non-equivalent control group design, involving 25 students in the experimental class and 28 students in the control class. The research instruments consisted of descriptive problem-solving tests (pretest and posttest) that had been validated and tested for reliability, as well as a problem-solving ability questionnaire. Data analysis was conducted using normality tests, homogeneity tests, the Independent Samples t-test, and N-Gain analysis with the assistance of SPSS version 27. The results showed that students in the experimental class achieved higher problem-solving skills than those in the control class, with mean posttest scores of 79.33 and 71.54, respectively. The t-test results indicated a calculated t-value of 2.198, which exceeded the critical t-value of 2.007 (df = 51). Furthermore, the significance value (two-tailed) was 0.033 < 0.05, indicating a statistically significant difference between the two groups. The N-Gain score of 56.71% was categorized as moderate, indicating that the implemented learning model had a moderate level of effectiveness. This finding was supported by the questionnaire results, which obtained an average score of 83.31, categorized as very good. Therefore, the Discovery Learning model supported by Google Sites effectively enhances students’ mathematical problem-solving skills and provides a more interactive, technology-integrated learning experience that can support teachers and curriculum developers in the digital era.